2000
DOI: 10.1161/01.str.31.10.2369
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of Early Endovascular Versus Surgical Treatment of Ruptured Cerebral Aneurysms

Abstract: Background and Purpose-This prospective study was conducted to compare the outcomes of surgical clipping and endovascular treatment in acute (Ͻ72 hours) aneurysmal subarachnoid hemorrhage (SAH). Methods-One hundred nine consecutive patients were randomly assigned to either surgical (nϭ57) or endovascular (nϭ52) treatment. Clinical and neuropsychological outcome was assessed at 3 and 12 months after treatment; MRI of the brain was performed at 12 months. Follow-up angiography was scheduled after clipping and 3 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

24
221
4
12

Year Published

2001
2001
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 365 publications
(261 citation statements)
references
References 65 publications
24
221
4
12
Order By: Relevance
“…Surgical skill level as assessed based on mortality rate The mortality rate for patients with ruptured cerebral aneurysms was 9.6% in the present study, lower than the 14-31% reported in Western countries 7,9,[11][12][13] and lower than the 8.8-48.5% in US studies that investigated relationships between case volume and outcome. 1,18) The mortality rate for patients with unruptured cerebral aneurysm was 0.2% in the present study, also lower than the 1.0-2.6% reported in Western countries.…”
Section: Discussioncontrasting
confidence: 69%
“…Surgical skill level as assessed based on mortality rate The mortality rate for patients with ruptured cerebral aneurysms was 9.6% in the present study, lower than the 14-31% reported in Western countries 7,9,[11][12][13] and lower than the 8.8-48.5% in US studies that investigated relationships between case volume and outcome. 1,18) The mortality rate for patients with unruptured cerebral aneurysm was 0.2% in the present study, also lower than the 1.0-2.6% reported in Western countries.…”
Section: Discussioncontrasting
confidence: 69%
“…Three contemporary prospective studies have compared coiling to clipping: the Finnish study, 13 ISAT, 17 and BRAT. 15 Based on their most recent follow-up, none of the 3 studies found a significant difference in rate of independent survival between the 2 treatments.…”
Section: To Clip or To Coil: Is That The Question?mentioning
confidence: 99%
“…13 Their enrollment continued, and altogether 138 patients were randomly assigned to microsurgical clipping (n = 71) or endovascular coiling (n = 67) by the end of 1999. No further follow-up of this trial has been published.…”
Section: To Clip or To Coil: Is That The Question?mentioning
confidence: 99%
See 1 more Smart Citation
“…In all other published prospective randomized trials [4][5][6]9 comparing clipping and coiling, equipoise was required before randomization. In contrast, the BRAT was an intent-to-treat trial that entered and randomized all patients with nontraumatic SAH before the source of the hemorrhage was determined.…”
Section: Discussionmentioning
confidence: 99%